Developmental safety of nirmatrelvir in zebrafish (Danio rerio) embryos. Issue 4 (14th November 2022) - Zizioli, Daniela; Ferretti, Sara; Mignani, Luca; Castelli, Francesco; Tiecco, Giorgio; Zanella, Isabella; Quiros‐Roldan, Eugenia
Abstract: Background: Nirmatrelvir, in combination with ritonavir, is one of the first orally available antiviral treatment for coronavirus disease 2019 (COVID‐19). Symptomatic pregnant women are at increased risk for severe illness and complications that can affect the developing baby. No malformations or lower embryo‐fetal survival have been observed when nirmatrelvir were administered to pregnant rats and rabbits. Safety evaluation of drugs used for treating COVID‐19 also in pregnancy is urgent for public health, then in this study we further investigated nirmatrelvir developmental toxicity using zebrafish as in vivo model. Material and Methods: Using the standardized Fish Embryo Toxicity (FET) test, we first determined the lethal concentration 50 (LC50), exposing embryos from gastrula stage up to 120 hr post fertilization (hpf) and daily recording lethality. Then, we exposed embryos to five doses comprising the human therapeutic one and up to the LC50 (25 μM). Morphology was evaluated at 72 and 120 hpf. Results: Nirmatrelvir did not affect survival rate and did not induce morphological defects up to the human therapeutic dose. Exposure at higher doses (2.4× and 3× the human C max ) however resulted in decreased hatching rate, reduced growth, slower heartbeat with pericardial edema, reduction of eye dimension, absence of the swim bladder and disruption of the anterior–posterior axis, with lack of tail detachment, spinal curvature and straight and smaller head. Conclusions: Our findings in zebrafish embryos add further information about developmental nirmatrelvir safety. Further studies are needed for pharmacological safety assessment of nirmatrelvir exposure during pregnancy.